2017
DOI: 10.20411/pai.v2i2.188
|View full text |Cite
|
Sign up to set email alerts
|

T-cell Responses in Individuals Infected with Zika Virus and in Those Vaccinated Against Dengue Virus

Abstract: Background The outbreak of Zika virus (ZIKV) infection in Brazil has raised concerns that infection during pregnancy could cause microcephaly and other severe neurodevelopmental malformations in the fetus. The mechanisms by which ZIKV causes fetal abnormalities are largely unknown. The importance of pre-infection with dengue virus (DENV), or other flaviviruses endemic to Brazil, remains to be investigated. It has been reported that antibodies directed against DENV can increase ZIKV infectivity by antibody depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
4
15
0
Order By: Relevance
“…Collectively, these results detail the global and cell type-specific innate immune responses during an acute ZIKV infection and highlight the rapid development of neutralizing Ab and effector memory T cell responses in a DENV experienced host. These data supports accumulating evidence that prior exposure to DENV accelerates and alters adaptive immune responses likely via the presence of cross-reactive epitopes [1619, 46]. Measuring time point- and cell type-specific transcriptional signatures of innate vs .…”
Section: Discussionsupporting
confidence: 83%
“…Collectively, these results detail the global and cell type-specific innate immune responses during an acute ZIKV infection and highlight the rapid development of neutralizing Ab and effector memory T cell responses in a DENV experienced host. These data supports accumulating evidence that prior exposure to DENV accelerates and alters adaptive immune responses likely via the presence of cross-reactive epitopes [1619, 46]. Measuring time point- and cell type-specific transcriptional signatures of innate vs .…”
Section: Discussionsupporting
confidence: 83%
“…In addition, our study using human leukocyte antigen (HLA) transgenic mice revealed that the immunodominance pattern of the CD8 + T cell response to ZIKV is altered by previous DENV infection ( 16 ). This is also consistent with human studies reporting that DENV-exposed individuals harbor T cells with cross-reactivity to ZIKV ( 8 10 , 34 ) and that DENV exposure before ZIKV infection influences the magnitude and kinetics of the CD8 + T cell response to subsequent ZIKV infection ( 8 ). Thus, both mouse and human studies demonstrate that DENV immunity affords cross-protection against ZIKV and shapes the anti-ZIKV CD8 + T cell response, and mouse studies provide direct evidence that CD8 + T cells protect against ZIKV infection, thereby providing the rationale to develop a protective CD8 + T cell–directed ZIKV vaccine.…”
Section: Introductionsupporting
confidence: 90%
“…Thus, at early stage of ZIKV infection, prior DENV exposure elicited cross-reactive CD8 + T cells with greater functional activity compared to those expanded during primary ZIKV infection. Recent studies using blood samples from non-pregnant individuals have identified cross-reactive CD8 + T cells in humans 47 , 48 . One of these studies showed that DENV exposure prior to ZIKV infection influenced the magnitude and quality of the CD8 + T cell response 47 , suggesting that prior DENV immunity may shape the anti-ZIKV CD8 + T cell response.…”
Section: Discussionmentioning
confidence: 99%